Neck Imaging Reporting and Data System: More Than Just a Template - Rhyner, P.A.; Bhatt, A.A.; Baugnon, K.L.; Aiken, A.H. (American Journal of Neuroradiology, 2022)
SUMMARY: The Neck Imaging Reporting and Data System (NI-RADS) is a guide developed and introduced in 2017 by head and neck radiologists who worked in an academic radiology department. Based on the Breast Imaging Reporting and Data System, the initial goals of NI-RADS were to make posttreatment head and neck cancer imaging dictations more succinct and efficient, guide treating physicians in the next appropriate steps when recurrence was suspected, and encourage institutional and national research. NI-RADS is more than a dictation template, and it is best instituted after a head and neck imaging practice is established. We support the use of NI-RADS once a radiologist understands the nuances of head and neck cancer, including the biology, common subsites involved, essentials of tumor staging, common posttreatment benign imaging appearances, and subtleties of recurrent disease.CECTcontrast-enhanced CTHNhead and neckHNChead and neck cancerNI-RADSNeck Imaging Reporting and Data SystemTBtumor board